Restoring mobility: Suspected spinal injury and rehabilitation in a white‐eared opossum (Didelphis albiventris, Lund, 1840) - Ichikawa, Ricardo Shoiti [UNESP]; Miranda, Mylena Oliveira [UNESP]; Rahal, Sheila Canevese [UNESP]; da Silva, Jeana Pereira [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Wiley, 2025)
Abstract This case report describes the evaluation and rehabilitation of a young white‐eared opossum ( Didelphis albiventris ) with a suspected thoracolumbar spinal cord injury after a predation event. The animal displayed lethargy, unresponsiveness and dragging of the hindlimbs. Neurological examination revealed diminished reflexes and the absence of deep pain perception. Radiographic imaging revealed no fractures. Computed tomography showed no changes in tissue density within the spinal canal and no evidence of mineralised disc material. Pharmacological treatment included mannitol, fluid therapy, analgesics, antibiotics and corticosteroids. Despite the absence of improvement in the neurological and motor response of the hindlimbs, a series of exercises for rehabilitation was conducted, leading to complete locomotion recovery after 35 days. However, deep pain perception remained absent. These findings suggest that while corticosteroids did not yield positive outcomes, intensive physiotherapy can enhance functional recovery. Future research should explore neuroplasticity mechanisms in opossums and other wildlife species to optimise rehabilitation strategies.